New decoupled empty substrate integrated waveguide realisation. Issue 17 (1st August 2017) - Sánchez, J.R.; Bachiller, C.; Esteban, H.; Belenguer, A.; Nova, V.; Boria, V.
Abstract : A novel decoupled empty substrate integrated waveguide (DESIW), which enables AC/DC decoupling in any device that is integrated in it is presented. The decoupling strategy is performed throughout a micro‐milling square pattern of easy implementation that increases the insertion losses compared with the standard ESIW. However, the DESIW related losses are still tolerable, allowing the employment of the new periodic structure in many practical applications. In particular, it can be used for the design and manufacturing of reconfigurable devices which need a bias voltage on the whole device, or just on some of its particular areas. A broadband transition from DESIW to microstrip planar lines has been also successfully designed. The new line has been manufactured and measured.